Water column raw data (Kongsberg EM 122 entire dataset) of RV MARIA S. MERIAN during cruise MSM125 - Miriam Römer; Yann Marcon; Mia Schumacher; Christian Borowski (PANGAEA, 2024)
Raw water column data were collected aboard RV MARIA S. MERIAN during cruise MSM125 using a Kongsberg EM 122 multibeam echosounder. The expedition took place during 30.01.2024 - 06.02.2024 from Algeciras (Spain) to Funchal (Portugal) in the Northern Atlantic. Data were recorded in the Moroccan and Portuguese EEZs and outside. MSM125 was a short cruise of only four working days to test deep-sea research devices developed at MARUM at the University of Bremen and the Max Planck Institute for Marine Microbiology, Bremen (MPIMM), as part of the Cluster of Excellence The Ocean Floor - Earth extquotesingles Uncharted Interface in in-situ operation so that they can be used in future research expeditions. The multibeam data provided here include a scientifically used part within the work area (2024-01-30T12:20:31 to 2024-02-04T10:55:51) and a transit part after leaving the work area and heading with fast vessel speed (10 kn) to the end harbour Funchal at Madeira (2024-02-04T10:55:51 to 2024-02-06T02:34:52). Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Data provision is part of the DAM Underway Project and according to the FAIR principles.